2011
DOI: 10.1016/j.bcp.2010.09.026
|View full text |Cite
|
Sign up to set email alerts
|

The anti-tumoral drug enzastaurin inhibits natural killer cell cytotoxicity via activation of glycogen synthase kinase-3β

Abstract: Please cite this article as: Ogbomo H, Biru T, Michaelis M, Loeschmann N, Doerr HW, Cinatl Jr. J, The anti-tumoral drug enzastaurin inhibits natural killer cell cytotoxicity via activation of glycogen synthase kinase-3␤, Biochemical Pharmacology (2008Pharmacology ( ), doi:10.1016Pharmacology ( /j.bcp.2010 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In vivo experiments in mice will be needed to address if the combination of Enzastaurin with a GSK3 inhibitor activates synergistic toxicities or if it has other off-target effects. For example, Enzastaurin is able to inhibit both natural and antibody-dependent cellular cytotoxicity of NK cells against tumor targets, and therefore may suppress NK cell-mediated activity against tumor cells(Ogbomo et al , 2011). Interestingly, treatment of NK cells with a GSK3 inhibitor reversed Enzastaurin-mediated inhibition of NK cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments in mice will be needed to address if the combination of Enzastaurin with a GSK3 inhibitor activates synergistic toxicities or if it has other off-target effects. For example, Enzastaurin is able to inhibit both natural and antibody-dependent cellular cytotoxicity of NK cells against tumor targets, and therefore may suppress NK cell-mediated activity against tumor cells(Ogbomo et al , 2011). Interestingly, treatment of NK cells with a GSK3 inhibitor reversed Enzastaurin-mediated inhibition of NK cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously shown that enzastaurin activates glycogen synthase kinase (GSK) 3β in natural killer cells and in turn reduces their activity [ 23 ]. To test the effects of (potential) anti-cancer agents in the context of cellular chemoresistance mechanisms, we have established the Resistant Cancer Cell Line (RCCL) collection, a collection of cell lines from 15 different cancer entities with acquired resistance to various cytotoxic and targeted anti-cancer drugs ( http://www.kent.ac.uk/stms/cmp/RCCL/RCCLabout.html ) including cell lines derived from the paediatric cancer entities neuroblastoma and rhabdomyosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Many complex natural products that inhibit the granule exocytosis pathway in CTLs and NK cells have been identified, but most are far too toxic or affect immune pathways other than perforin-mediated cytotoxicity to be useful clinically. These include cytochalasin D (blocks actin polymerization and prevents transferal of the cytotoxic granules to the plasma membrane); antimycin A and oligomycin A (inhibitors of cell respiration); FD-891, gliotoxin, and chebulagic acid (prevent formation of the immune synapse); and calphostin C, herbimycin A, costunolide, FK506, staurosporine, and enzastaurin (protein kinase inhibitors that block early signal transduction through the T cell receptor pathway). The only agents that have been shown to directly affect the concentration of perforin within the cytotoxic granules are those that act by inhibition of the vacuolar-type (H + ) adenosinetriphosphatases (V-ATPases) that regulate lysosomal (and, therefore, CSV) pH, but these reagents adversely affect the function of many cell types other than CTLs and NK cells. Cytotoxic granules are specialized organelles that require a pH ∼5.5 within the lumen, and V-ATPases are proton pumps responsible for generating and maintaining this acidic environment. , V-ATPase inhibitors can increase lumen pH, resulting in a significant reduction of perforin content together with morphological changes in the lytic granules .…”
Section: Small Molecule Inhibitors Of Perforinmentioning
confidence: 99%